FOCUS STUDY ON HALAL TOURISM PROMOTION - Fadli Agus Triansyah (JASIE, 2023)
Halal tourism is a type of tourism that follows the rules and principles of Islamic sharia. This includes services and facilities designed to meet the needs of Muslim travelers, such as Halal food, access to mosques or places of worship, separate accommodation for men and women, and recommended modest dress. This study utilised a systematic review on halal tourism promotion scopus database from 2021-2023. In this research, the keyword used is